A Utilização de Derivativos Financeiros e a Valorização de Empresas Brasileiras listadas na B3: Uma análise sob a ótica da teoria moderna de finanças. - Marques, Leandro (2023)
This study focused on analyzing the impact of using derivatives as hedge on the market value of Brazilian companies. The calculation of Tobin's Q, based on a combination of the approaches by Lewellen and Badrinath (1997) and the Market-to-book approximation by Chung and Pruitt (1994), provided a solid metric to assess the market value of companies. The fixed effects regression model applied in the analyses offered a consistent statistical framework for examining the relationships between hedge usage and company value, taking into consideration other relevant variables. Furthermore, the study explored variables that might influence this relationship, including company size, financial constraints, leverage levels, profitability, and growth opportunities. The analysis of these factors provided a more complete understanding of the dynamics affecting the value of Brazilian companies. The results indicated that the efficient use of derivatives as hedge adds value to companies, supporting the hypothesis that a higher level of hedging is related to a greater valuation of entities. This aligns with previous studies that also highlighted the positive contribution of hedge usage in risk management and value creation. However, the conclusions also revealed that some factors might impact this relationship in a way contrary to expectations. For example, company size and financial leverage showed results that were not in line with initial expectations. These findings point to the complexity of the dynamics involved in determining the market value of companies and highlight the need for further in-depth analysis in future research. These discoveries help to better understand how hedge usage affects the value of companies in a Brazilian context. Additionally, they contribute to the existing body of knowledge on the subject, highlighting the provision of tangible evidence on the relationship between the level of hedging and financial performance. The phenomenon portrayed contributes to the validation of modern finance theory, as well as influences the optimal capital structure. The results of this work contribute to the financial sustainability of companies, providing greater stability and confidence in financial performance. Despite the contributions of this study, it is important to highlight its limitations. The study was delimited to Brazilian companies, and the results may not be directly applicable to other geographical or economic contexts. For future research, it is recommended to expand the scope to include companies from different countries and regions, in order to assess the generalization of the conclusions. Moreover, an in-depth investigation of the reasons behind the observed relationships, especially regarding the control variables, could provide additional contributions. The continuation of the study and the exploration of other variables and financial metrics could also enrich the understanding of the complex interactions between hedge usage and company value.